Potential evaluation study and application method for biomass energy from agricultural by-products (rice, com , peanut) in Nam Dinh Province - Hai, Luu Duc; Quy, Tran Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 2, 2009)
Abstract